2022
DOI: 10.1021/acsestwater.1c00386
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Hazards of Antibiotic Resistance in Wastewater-Impacted Streams during Low Instream Flow Conditions

Abstract: Wastewater treatment plants (WWTPs) are a major point source of antibiotics and antimicrobial resistance in the aquatic environment. This study evaluated model predictions for ciprofloxacin (CIP), erythromycin, and sulfamethoxazole (SMX) concentrations, and the potential presence of their respective resistance within U.S. streams affected by WWTP discharges under varying instream flow conditions. We incorporate predicted no-effect concentrations (PNECs) for selection resistance into the previously developed De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…There may be many other native species that are imperiled but remain understudied and have not yet received the attention or momentum necessary to begin the listing process. We also acknowledge that effluent may contain contaminants, in particular endocrine disruptors, antibiotics, and other pharmaceuticals, that escape treatment and result in concentrations that exceed safety thresholds (Ankley et al., 2007; Kamanmalek et al., 2022; Rice & Westerhoff, 2017). There is scant understanding of the prevalence, duration, and effects of these pollutants on at‐risk species which create trade‐offs on the quantity and quality of flow in effluent in streams.…”
Section: Discussionmentioning
confidence: 99%
“…There may be many other native species that are imperiled but remain understudied and have not yet received the attention or momentum necessary to begin the listing process. We also acknowledge that effluent may contain contaminants, in particular endocrine disruptors, antibiotics, and other pharmaceuticals, that escape treatment and result in concentrations that exceed safety thresholds (Ankley et al., 2007; Kamanmalek et al., 2022; Rice & Westerhoff, 2017). There is scant understanding of the prevalence, duration, and effects of these pollutants on at‐risk species which create trade‐offs on the quantity and quality of flow in effluent in streams.…”
Section: Discussionmentioning
confidence: 99%
“…Tab. 1 [40][41][42][43][44][45][46][47] lists the classification, toxicity, and environmental residual concentration of some common antibiotics. The chemical structures of commonly used antibiotics are illustrated in Fig.…”
Section: Human and Environmental Risks Of Antibioticsmentioning
confidence: 99%
“…A recent study of AR in US streams affected by WWTP discharges under varying instream flow conditions found that under low instream flow conditions, 26% of the streams did not meet the AR safety threshold for ciprofloxacin (CIP) and erythromycin (ERY) [ 7 ]. It is important to note that 5% of the dose of ERY is excreted in the active form in the urine and that ERY is recalcitrant to different treatments in WWTPs, with wastewater from WWTPs, pharmaceutical facilities, and hospitals being the main contributors to the spread of ERY [ 8 ].…”
Section: Introductionmentioning
confidence: 99%